2009
DOI: 10.1007/s10534-009-9237-0
|View full text |Cite
|
Sign up to set email alerts
|

Siderophores of Marinobacter aquaeolei: petrobactin and its sulfonated derivatives

Abstract: Siderophores are low molecular weight, high-affinity iron(III) ligands, produced by bacteria to solubilize and promote iron uptake under low iron conditions. Two prominent structural features characterize the majority of the marine siderophores discovered so far: (1) a predominance of suites of amphiphilic siderophores composed of an iron(III)-binding headgroup that is appended by one or two of a series of fatty acids and (2) a prevalence of siderophores that contain α-hydroxycarboxylic acid moieties (e.g., β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…To our knowledge, ABC transporters of sulfonated siderophores have not been characterized. However, members of the Marinobacter genus have been shown to synthesize a sulfonated siderophore (36,37). It is possible that CD2992-2989 has specificity for a sulfonated derivative of a siderophore.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, ABC transporters of sulfonated siderophores have not been characterized. However, members of the Marinobacter genus have been shown to synthesize a sulfonated siderophore (36,37). It is possible that CD2992-2989 has specificity for a sulfonated derivative of a siderophore.…”
Section: Discussionmentioning
confidence: 99%
“…A Chrome Azurol S assay showed that both Phaeobacter strains excrete siderophores under iron-limiting conditions, whereas Roseobacter denitrificans, which lacks the gene cluster, shows no excretion (Figure 4). The organization of the gene cluster is identical to that of the asbABCDEF petrobactin biosynthesis locus of Bacillus anthracis and Marinobacter aquaeoeli VT8 (Pfleger et al, 2007;Homann et al, 2009). The only difference is that asbC and asbD are fused in P. gallaeciensis (Figure 4).…”
Section: Geis Prophages and Gene-transfer Agents (Gtas)mentioning
confidence: 98%
“…In comparison, the iron-reducing Shewanella oneidensis MR-1 has 66 cytochromes (1.46% of the proteincoding genes), 13 of which are predicted to function as (per)oxidases in the outer membrane and potentially as extracellular proteins. Marine amphiphilic siderophores involved in the acquisition of iron have previously been isolated from VT8 (27). The genome of VT8 harbors several candidate genes with a potential function in iron acquisition via siderophores, uptake through permeases, and redox activity.…”
Section: Acquisition Of Carbonmentioning
confidence: 99%